PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI CERDAS (MONDAS) UNTUK MENINGKATKAN BERPIKIR KREATIF PADA MATA PELAJARAN IPS - Abdul Zabar Muhamad Zamaludin; Nanan Abdul Manan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The development of intelligent monopoly learning media (MONDAS) aims to determine the level of media validity and the results of development media trials in improving creative thinking in social studies learning. Researchers use an R&D research design with the ADDIE model. The product trial subjects were 27 class IV students at SDN 3 Pakemitan. Data collection instruments use questionnaires, interviews, observations and tests. The results of research on intelligent monopoly learning media (MONDAS) show valid criteria with a score of 92.5% from media experts, and 92.5% from material experts. Media monopoly can also improve the creative thinking of students in the very good category with an average score of 85%. Teachers and students gave positive responses to the media developed with evidence of a score of 72.5% for teacher responses and 91.62% for student responses. Thus, it can be concluded that intelligent monopoly learning media (MONDAS) is suitable for use as a learning medium to improve creative thinking in social studies lessons for class IV students at SDN 3 Pakemitan. Pengembangan media pembelajaran monopoli cerdas (MONDAS) bertujuan untuk mengetahui bagaimana tingkat validitas media dan hasil uji coba pengembangan media dalam meningkatkan berpikir kreatif pada pembelajaran IPS. Peneliti menggunakan desain penelitian R&D dengan model ADDIE. Subjek uji coba produk yaitu peserta didik kelas IV SDN 3 Pakemitan sebanyak 27 siswa. Instrumen pengumpulan data menggunakan angket, wawancara, observasi dan tes. Hasil penelitian media pembelajaran monopoli cerdas (MONDAS) menunjukan kriteria valid dengan perolehan skor 92,5% dari ahli media, dan 92,5% dari ahli materi. Media monopoli juga dapat meningkatkan berpikir kreatif siswa kategori sangat baik dengan perolehan nilai rata-rata 85%. Guru dan Siswa memberikan respon fositif terhadap media yang dikembangakan dengan bukti dari perolehan skor sebesar 72,5 % untuk respon Guru, dan 91,62% untuk respon siswa. Dengan demikian dapat disimpulkan bahwa media pembelajaran monopoli cerdas (MONDAS) layak digunakan menjadi media pembelajaran untuk meningkatkan berpikir kreatif pada pelajaran IPS siswa kelas IV SDN 3 Pakemitan.